A model for a participative approach to digital competition regulation - Christophe Carugati (Bruegel, 2023)
Digital competition regulations often put in place participative approaches to ensure competition in digital markets. The participative approach aims to involve regulated firms, stakeholders and regulators in the design of compliance measures. The approach is particularly relevant in complex and fast-evolving digital markets, where whole industries often depend on the behaviours of the regulated firms. The participative approach enables stakeholders and regulated firms to design compliance measures that are optimal for all because they ensure legal certainty for regulated firms, save time for regulators and take into account the views of stakeholders. However, the participative approach is subject to regulatory capture. The regulated firms and stakeholders might try to promote their interests to the regulator. This could result in endless discussions at best, and the adoption of inappropriate solutions following intense lobbying at worst. A governance model is necessary to ensure that the participative approach works without risks of regulatory capture. The model should define clearly each participant's role, duties and rights. There should be: 1) equal and transparent access of all stakeholders to the dialogue; 2) the presentation of tangible and evidence-based solutions from stakeholders and regulated firms; 3) public decisions from the regulator that contain assessments of the proposed solutions, with guidance to clarify rules; and 4) compliance measures proposed by the regulated firm in line with the guidance. The model should provide an assessment framework for the proposed solutions to identify the most effective. The assessment should rely on the principle of proportionality to assess whether the proposed compliance measure is proportionate, to ensure the effectiveness of the regulation. Finally, the model should safeguard against regulatory capture thanks to transparency rules and external monitoring.
Keywords: 330